Creative Economic Empowerment of Wool and Polyester Hand Craft at the Bina Sejahtera Orphanage Palangka Raya - Rahman, Nur Fuadi; Safitri, Novi Angga; Arifin, Muhammad Zainal; Syarifuddin; Riza Hafizi, Muhammad (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2022)
The COVID-19 pandemic gave birth to a policy of learning from home or online learning. This policy raises various problems, one of which is saturation in online learning activities. This boredom is also felt by the children of the Bina Sejahter Orphanage because they only focus on studying at home (the orphanage) and they have a lot of free time left. Free time that is owned by the children in the orphanage that can be used for useful things, one of which is making handicrafts. One of the handicrafts that produce economic value, namely handicrafts from wool and polyester yarn. From wool and polyester we can make various kinds of handicrafts such as flowers, flower pots, key chains, souvenirs, brooches, mask hooks, wall hangings, knitting bags, and others. For this reason, the implementers of community service activities of the Syari'ah Economics Study Program, Faculty of Economics and Islamic Business IAIN Palangka Raya carry out community service by providing Creative Economy Empowerment Assistance for Handicrafts from Wool and Polyester Yarn at the Bina Sejahtera Orphanage, Palangka Raya City. The children and also the caretaker of the orphanage were very enthusiastic about participating in the activities held.